Răspuns :
3^x² - 3x = 81
3^x² - 3x = 3^4
x² - 3x = 4
x² - 3x - 4 = 0
Se formeaza o ecuatie de gradul al II-lea
ax² + bx + c = 0 unde folosim formula
x = - b + √ b² - 4ac / 2a
x = - b - √ b² - 4ac / 2a
x = - ( -3) + √(-3)² - 4 * 1 * ( -4) / 2*1
x = - ( -3) - √(-3)² - 4 * 1 * ( -4) / 2*1
x = 3 + √9 + 16 /2
x = 3 - √9+16 /2
x = 3 + √25 /2
x = 3 - √25 /2
x = 3 + 5 /2 ⇒ x = 4
x = 3 - 5 /2 ⇒ x = -1 ∉ N
Solutia finala este x = 4
3^x² - 3x = 3^4
x² - 3x = 4
x² - 3x - 4 = 0
Se formeaza o ecuatie de gradul al II-lea
ax² + bx + c = 0 unde folosim formula
x = - b + √ b² - 4ac / 2a
x = - b - √ b² - 4ac / 2a
x = - ( -3) + √(-3)² - 4 * 1 * ( -4) / 2*1
x = - ( -3) - √(-3)² - 4 * 1 * ( -4) / 2*1
x = 3 + √9 + 16 /2
x = 3 - √9+16 /2
x = 3 + √25 /2
x = 3 - √25 /2
x = 3 + 5 /2 ⇒ x = 4
x = 3 - 5 /2 ⇒ x = -1 ∉ N
Solutia finala este x = 4